2017
DOI: 10.5897/jat2017.0267
|View full text |Cite
|
Sign up to set email alerts
|

The role of taxpayer awareness, tax regulation and understanding in taxpayer compliance

Abstract: The purpose of this study is to provide an insight into the government's need for sustainable socialization on the importance of paying taxes. This study also aims to analyze the taxpayer's awareness, whether it can mediate the knowledge and understanding of tax regulations on taxpayer compliance or not. The approach in this study is quantitative, with taxpayers as the respondents. The results show that knowledge and understanding of tax regulation and awareness of taxpayers simultaneously contribute to taxpay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 6 publications
3
21
0
5
Order By: Relevance
“…This negates the findings of Nugroho and Zulaikha (2012); Vadde and Gundarapu (2012) while it reaffirms the findings of Abdul-Razak and Adafula (2013). The quality of tax services has significant factors on voluntary tax compliance, which is in line with the studies of Rahayu et al (2017); Nsubuga, Sai, and Naatu (2017) and Al-Maghrebi, Ahmad, and Palil (2016).…”
Section: Discussion Of Findingssupporting
confidence: 76%
See 1 more Smart Citation
“…This negates the findings of Nugroho and Zulaikha (2012); Vadde and Gundarapu (2012) while it reaffirms the findings of Abdul-Razak and Adafula (2013). The quality of tax services has significant factors on voluntary tax compliance, which is in line with the studies of Rahayu et al (2017); Nsubuga, Sai, and Naatu (2017) and Al-Maghrebi, Ahmad, and Palil (2016).…”
Section: Discussion Of Findingssupporting
confidence: 76%
“…The findings from the study showed that taxpayers' awareness has a positive mediating effect on tax ID number expediency, service quality and tax payer's compliance while it has a negative mediating role on the relationship between tax knowledge, tax socialisation and tax payer's compliance. In addition, Rahayu, Setiawan, and Troena (2017) examined the roles of taxpayers' awareness, tax regulation and understanding and influences on taxpayers' compliance. The findings from the study showed that knowledge and understanding of tax regulations and tax awareness of the tax laws by tax payers made a significant contribution to tax payers' compliance but did not have significant influence on compliance.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Semakin kompleks tingkat pemahaman wajib pajak terkait ketentuan yang ada maka ketaatannya dalam menjalankan kewajiban perpajakan akan semakin bertambah. Peraturan perpajakan juga berpengaruh terhadap kepatuhan dimana kontribusi pemahaman yang didasarkan atas peraturan perundang-undangan memiliki sifat yang memaksa (Yayuk et al, 2017). Hasil yang berbeda diperoleh dalam penelitian Arisandy (2017) dan Pebrina & Hidayatulloh (2020) yang menunjukan bahwa pemahaman peraturan perpajakan tidak berpengaruh pada kepatuhan wajib pajak.…”
Section: Tabel 1 Jumlah Wajib Pajak Yang Membayar Dan Menunggak Pkb DIunclassified
“…The substance of monitoring is to make certain that AR conveys the philosophy and regulations that are quintessential to the Tax Provisions and Procedures to taxpayers. Taxpayer compliance is carefully associated with the offerings furnished by tax provider officers (Yayuk, Ngesti et al, 2017) due to the fact all activities and things to do of tax carrier officers noticeably affect taxpayer compliance. AR as one part of the service of the tax office has a function as a liaison between the Directorate General of taxes and taxpayers so that it greatly affects the protection of nation revenues (Rachmawan et al, 2020)…”
Section: Effective Compliance Monitoring and Verificationmentioning
confidence: 99%